The Association of Reactive Oxygen Species with High-Risk Human Papilloma Virus Infection and Some Sperm Parameters in a Samples of Iraqi Idiopathic Infertile Males (Iraqi Journal of Medical Sciences, 2024)
Background: Male infertility is a prevalent issue affecting couples worldwide. Human Papillomavirus (HPV) is known to cause cervical cancer in women, but its association with male infertility is gaining attention. High-risk HPV (HR-HPV) infection has been linked to oxidative stress (OS), an imbalance of reactive oxygen species (ROS) in the body. This OS may impact sperm function and fertility in men.Objective: To find out the association of ROS with HR-HPV infection and sperm parameters with group of infertile Iraqi patients with unknown causes. Methods: A case-control study of 68 seminal fluid samples (34 fertile and 34 infertile males) submitted to real time polymerase chain reaction (PCR) for detection of HR-HPV types (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68) and the plasma of seminal fluid samples were tested for ROS by using enzyme-linked immunosorbent assay (ELISA).Results: The outcomes showed high statistically significant association of ROS level with sperm parameters and HR-HPV infection (P
Keywords: High risk human papillomavirus; idiopathic infertility; sperm parameter; reactive oxygen species